PEMBERONTAKAN TERHADAP BUDAYA PATRIARKI DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO FEMINISME HENRIETTA L. MOORE - Vivi Saputri; Elsa Mulya Karlina (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This research is entitled "Resistance to Patriarchal Culture in the Novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo: A Henrietta L. Moore Feminist Study.” The purpose of this study is to describe the forms of patriarchal culture and the forms of resistance carried out by the female protagonist against patriarchal practices in the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo. This research employs a literary psychology approach using Henrietta L. Moore’s feminist theory, which focuses on gender relations, female subordination, male domination, gender inequality, and women's struggles to achieve autonomy and freedom. The research method used is qualitative with a library research design. The data consist of quotations, dialogues, narrations, and monologues found in the novel. Data were collected through documentation techniques by reading, recording, and classifying the data according to the research focus. The results of the study indicate that the novel represents patriarchal culture through practices such as forced marriage by abduction (kawin tangkap), the subordination of women, restrictions on women’s rights to make life choices, and male domination in decision-making processes. Furthermore, the forms of resistance demonstrated by the female protagonist include rejecting the practice of kawin tangkap, voicing opposition to gender injustice, fighting for bodily autonomy and personal freedom, asserting the right to determine her own future, and challenging cultural norms that perpetuate the oppression of women. This study reveals that women possess the ability to resist patriarchal systems and reclaim their rights through self-awareness, courage, and social support. Therefore, the novel serves as a representation of women's struggles against patriarchal domination and gender-based oppression.